Outer Space Treaty (OST) - blueprint for “peaceful uses” or pitfall for future conflict? - Miron, Samih Zaman (Cranfield University Defence and Security, 2024)
The Outer Space Treaty (OST) was enacted in 1967 in the context of the ‘Space Race’ between the US and the USSR, accelerated following the USSR’s launch of Sputnik in 1957. In recent years, rapid development of technology has enabled significant increase in the extent of activities in Space, resulting in many more States getting involved in the Space sector and the opening up of commercial activities that include the private sector. Thus, there has been a corresponding increase in the possibility of conflict arising from activities in Space, whether intentional or by mistake. Although there have been some initiatives in working on codes and guidance in the conduct of activities in Space, the position in key areas of conduct, accountability and enforcement has still to be clarified. This has important implications on the Laws of Armed Conflict (LOAC) given the increased risk of conflict and the particular characteristics of Space. This study will evaluate the “peaceful uses” wording in the OST through an International Relations (IR) lens and drawing on Comparative Adaptive Systems theory as to its context and subsequent practice.
Keywords: OST; Outer Space Treaty; IR; international relations; Complex Adaptive Systems